2014
DOI: 10.1097/mat.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Use of TandemHeart Percutaneous Ventricular Assist Device in Surgical Repair of Postinfarction Ventricular Septal Defect

Abstract: Mortality for patients presenting with acute myocardial infarction (AMI) complicated by ventricular septal defect (VSD) and cardiogenic shock is very high even with surgical repair. We report our experience regarding utilization of TandemHeart, a percutaneous ventricular assist device (pVAD) as an adjunct to the treatment of these patients. Retrospective case series study design included a total of 11 patients with post-AMI VSD and severe refractory cardiogenic shock who received pVAD support at our institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 11 publications
5
22
0
Order By: Relevance
“…Alternative mechanical circulatory support (MCS) devices have been used in small series for postinfarct VSD. These include Impella,27–29 TandemHeart30 and veno-arterial extra corporeal membrane oxygenation (VA-ECMO) 31 32. A computer simulation model to evaluate the effectiveness of different MCS devices for postinfarct VSD33 found that no device normalised haemodynamics, and the ratio of pulmonary to systemic flow (Qp:Qs ratio) could not be reduced below 2.0.…”
Section: Undertaking the Proceduresmentioning
confidence: 99%
“…Alternative mechanical circulatory support (MCS) devices have been used in small series for postinfarct VSD. These include Impella,27–29 TandemHeart30 and veno-arterial extra corporeal membrane oxygenation (VA-ECMO) 31 32. A computer simulation model to evaluate the effectiveness of different MCS devices for postinfarct VSD33 found that no device normalised haemodynamics, and the ratio of pulmonary to systemic flow (Qp:Qs ratio) could not be reduced below 2.0.…”
Section: Undertaking the Proceduresmentioning
confidence: 99%
“…Current guidelines for cardiac surgery in heart failure patients recommend preparation for MCS as salvage therapy, with no data to recommend preoperative use [1,2]. Preoperative ECMO before repair of structural heart disease has been described in isolated reports [21][22][23][24][25]. Few of the existing reports present ECMO as a means to improve postoperative outcome, none taking full advantage of organ recovery, diuresis, nutrition, or patient mobilization.…”
Section: Commentmentioning
confidence: 99%
“…Few of the existing reports present ECMO as a means to improve postoperative outcome, none taking full advantage of organ recovery, diuresis, nutrition, or patient mobilization. One series from Gregoric and colleagues [25] compared 8 patients that received a percutaneous assist device (TandemHeart, LivaNova, Houston, TX) before repair of ischemic VSD with 3 patients that required the device postoperatively. They demonstrated markedly improved survival as well as physiologic improvement with preoperative MCS support.…”
Section: Commentmentioning
confidence: 99%
“…In the overall population undergoing surgical VSD repair, there is a significant survival advantage in delaying surgery for at least seven days (1). However, during the waiting period, the risk is high for developing cardiogenic shock or expansion of the VSD to the point of being inoperable (5).…”
mentioning
confidence: 99%